(untitled) (Economics and region, 2025)
This article examines the theoretical foundations and practical applications of strategic controlling in the system of financial stability management of enterprises in the metallurgical industry. In modern conditions of economic uncertainty, increasing global risks, and energy market volatility, the issue of maintaining long-term financial resilience becomes critically important, especially for capital-intensive and export-oriented sectors such as metallurgy. The study highlights the need to adapt controlling tools to the specific characteristics of the industry and substantiates the role of strategic controlling as a key element in enhancing managerial decision-making and risk anticipation capabilities. The authors conduct a comparative analysis of the maturity of controlling systems at two representative metallurgical enterprises—Metinvest (Ukraine) and Baku Steel Company (Azerbaijan). The analysis focuses on the implementation of ERP systems, the use of KPI and BSC, the level of integration with budgeting and risk management, as well as the degree of reporting automation and transparency. The results reveal substantial differences in the development and institutionalization of strategic controlling processes, which directly affect the ability of enterprises to ensure financial sustainability in the face of external shocks. The paper also provides a set of practical recommendations for strengthening strategic controlling at the sectoral level. Among these are the establishment of centralized controlling departments, the integration of controlling into strategic risk management frameworks, the alignment of internal reporting with international management accounting standards (such as IFRS for Management), and the development of continuous professional education programs for enterprise managers. These measures are aimed at building an integrated management system capable of ensuring both operational efficiency and strategic adaptability. The conclusions of the study serve as a basis for further scientific research in the field of industrial finance and controlling and may be used by practitioners in developing regulatory and organizational instruments for enhancing financial sustainability and strategic planning at metallurgical enterprises.